QUANTITATIVE ANALYSIS OF CYTISINE IN THERMOPSIS ALTERNIFLORAE USING HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY - GADHVI, KRUPA; MODI, KARUNA; SHAH, MAMTA (International Journal of Current Pharmaceutical Research, 2023)
Objective: An optimized high-performance thin-layer chromatography (HPTLC) method has been established for the quantification of cytisine in Thermopsis alterniflorae Regel and Schmalh. Methods: Alcoholic extract of the aerial parts were prepared using Soxhlet extraction method. Separation was achieved on silica gel 60 F254 HPTLC plates using toluene-ethyl acetate-diethyl amine (7:2:1, v/v) as the mobile phase. The quantitation of cytisine was carried out using densitometric scanning at 545 nm after derivatization using Dragendorff’s reagent. Results: The linear regression analysis data for the calibration plot showed a good linear relationship (r2 = 0.9849) in the concentration range 10 to 15 µg/spot. The method was validated for precision, repeatability, accuracy, specificity, limit of detection and limit of quantification. The average recovery was 99.0899% indicating good accuracy. The percentage yield of cytisine obtained was 0.5075+0.0135 % w/w. Conclusion: The proposed HPTLC method was found to be simple, sensitive, accurate, reproducible, and robust.